2015
DOI: 10.15376/biores.10.4.8295-8311
|View full text |Cite
|
Sign up to set email alerts
|

Selective Analytical Production of 1-Hydroxy-3,6-dioxabicyclo[3.2.1]octan-2-one from Catalytic Fast Pyrolysis of Cellulose with Zinc-Aluminium Layered Double Oxide Catalyst

Abstract: Zinc-aluminium layered double oxide (Zn-Al-LDO) catalysts derived from layered double hydroxides (LDHs) were prepared and used for the catalytic fast pyrolysis of cellulose to selectively produce 1-hydroxy-3,6-dioxabicyclo[3.2.1]octan-2-one (LAC), which is a valuable anhydrosugar derivative. Analytical pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) experiments were performed to investigate the LAC production under different reaction conditions. The results indicated that the Zn-Al-LDO catalysts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Similarly, Palinko et al reported higher BET surface area in Mg–Al mixed-metal oxides compared to Zn–Al mixed-metal oxide . An increase in surface area with increasing Al content has been attributed to increased porosity generated by greater CO 2 gas evolution during the calcination of the LDH precursor material caused by decomposition of CO 3 2– . , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Palinko et al reported higher BET surface area in Mg–Al mixed-metal oxides compared to Zn–Al mixed-metal oxide . An increase in surface area with increasing Al content has been attributed to increased porosity generated by greater CO 2 gas evolution during the calcination of the LDH precursor material caused by decomposition of CO 3 2– . , …”
Section: Resultsmentioning
confidence: 99%
“…These diffraction patterns are in agreement with those of previously reported Zn−Al and Mg−Al mixed metal oxides which were prepared by calcination in the range of 450−500 °C. 13,28,29 The Mg−Al and Zn−Al materials show broad diffraction peaks indicative of crystalline MgO and ZnO, respectively. We were unable to detect crystalline alumina (Al 2 O 3 ) or spinel-type (MAl 2 O 4 , M = Mg or Zn) phases in any of the materials.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…These diffraction patterns are in agreement with those of previously reported Zn-Al and Mg-Al mixed metal oxides which were prepared by calcination in the range of 450-500 °C. 13,[28][29] The Mg-Al and Zn-Al materials show broad diffraction peaks indicative of crystalline MgO and ZnO, respectively. We were unable to detect crystalline alumina (Al2O3) nor spinel-type (MAl2O4, M = Mg or Zn) phases in any of the materials.…”
Section: Resultsmentioning
confidence: 99%
“…30 An increase in surface area with increasing Al content has been attributed to increased porosity generated by greater CO2 gas evolution during the calcination of the LDH precursor material caused by decomposition of CO3 2-. 16,29 We used CO2-TPD to compare basic site density and strength among the different mixed-metal oxides (Table 1 and Figure S2). Three peaks occurring at low, medium, and high temperatures were resolved from the desorption curves.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a more attractive technique, catalytic pyrolysis of biomass toward specific compounds through selective control of biomass pyrolysis process (known as selective pyrolysis) has gained extensive attentions, as it offers a promising way to facilitate the application of pyrolytic products (Theodore and Juan, 2013 ; Liu et al, 2014a ; Shen et al, 2015 ; Zhang et al, 2017 ). Such catalytic/selective pyrolysis can be achieved via suitable biomass materials or proper catalysts under specific pyrolysis conditions, so as to obtain different valuable compounds, such as levoglucosenone (Lu et al, 2014 ; Zhang et al, 2015d ; Ye et al, 2017 ), furfural (Lu et al, 2011 ; Zhang et al, 2014 ), 1-hydroxy-3,6-dioxabicyclo[3.2.1]octan-2-one (Fabbri et al, 2007 ; Zhang et al, 2015a ), aromatic hydrocarbons (Vichaphund et al, 2015 ), 4-vinyl phenol (Qu et al, 2013 ), 4-ethyl phenol (Zhang et al, 2015c ; Lu et al, 2016 ), 4-ethyl guaiacol (Lu et al, 2017 ), nicotyrine (Ye et al, 2016 ) and so on.…”
Section: Introductionmentioning
confidence: 99%